NSUN2-mediated RNA m5C modification modulates uveal melanoma cell proliferation and migration. Issue 8 (3rd August 2022) - Luo, Guangying; Xu, Weiwei; Chen, Xiaoyan; Wang, Siqi; Wang, Jiao; Dong, Feng; Hu, Dan-Ning; Reinach, Peter S.; Yan, Dongsheng
ABSTRACT: RNA 5-methylcytosine (m 5 C) is a widespread post-transcriptional modification involved in diverse biological processes through controlling RNA metabolism. However, its roles in uveal melanoma (UM) remain unknown. Here, we describe the biological roles and regulatory mechanisms of RNA m 5 C in UM. Initially, we identified significantly elevated global RNA m 5 C levels in both UM cells and tissue specimens using ELISA assay and dot blot analysis. Meanwhile, NOP2/Sun RNA methyltransferase family member 2 (NSUN2) was upregulated in both types of these samples, whereas NSUN2 knockdown significantly decreased RNA m 5 C level. Such declines inhibited UM cell migration and suppressed cell proliferation through cell cycle G1 arrest. Furthermore, bioinformatic analyses, m 5 C-RIP-qPCR, and luciferase assay identified β-Catenin (CTNNB1) as a direct target of NSUN2-mediated m 5 C modification in UM cells. Additionally, overexpression of miR-124a in UM cells diminished NSUN2 expression levels indicating that it is an upstream regulator of this response. Our study suggests that NSUN2-mediated RNA m 5 C methylation provides a potential novel target to improve the therapeutic management of UM pathogenesis.